Nonemergent craniotomy surgical site infection: a retrospective cohort study - Bruno Tiago Correia Barbosa Pinto Ribeiro (2020)
Background: The incidence of surgical site infection after craniotomy (SSI-CRAN) varies widely and is associated with major consequences. The aim of this study is to estimate the SSI-CRAN rate at the neurosurgery department of a tertiary center and to establish its risk factors. Methods: All consecutive adult patients who underwent nonemergent craniotomy at a tertiary center from January 2018 to October 2019 were retrospectively assessed. Demographic, clinical and surgical data were collected. The main outcome of our study was the development of SSI within 30 days post-surgery, as defined by the European Centre for Disease Prevention and Control (eCDC) guidelines. Univariate and multivariate analysis was performed to establish risk factors for SSI-CRAN. Results: From the 271 patients enrolled in this study, 15 (5.5%) developed SSI-CRAN within 30 days post-surgery, 11 (73.3%) of which were organ-space. The most common causative microorganisms were gram-positive cocci, particularly S. epidermidis (n=4, 66.7%). In the univariate analysis, absence of normothermia (60.0% vs. 15.8% in the group with SSI-CRAN and in the group without SSI-CRAN, respectively; p < 0.001) and cerebrospinal (CSF) leakage (40.0% vs. 2.4%; p < 0,001) were associated with SSI-CRAN. In the multivariate analysis, normothermia (OR = 0.200, 95% CI [0,058-0,687]; p = 0.011) was the only protective factor and CSF leakage (OR = 12.152, 95% CI [2,684 - 55,010]; p= 0.001) was the only independent risk factors for SSI-CRAN. Conclusion: The cumulative incidence of SSI-CRAN within 30 days post-surgery was 5.5%. CSF leakage and the absence of normothermia were the only independent risk factors for SSI-CRAN. The data provided in this study can be considered in the design of preventive strategies aimed to reduce the incidence of surgical site infection.